Educação infantil, distorções e crescimento econômico - Delalibera, Bruno Ricardo (2014)
The objective of this work is to understand, from the perspective of education, the divergence in per capita income and the convergence of schooling among the sub-Saharan and European countries between 1960 and 2010. This study uses a general equilibrium model where there are two sectors in the economy and homogeneous consumers who choose consumption, formal education and early childhood education. According to the results of the work, despite the evolution of early childhood education for the countries of sub-Saharan those countries did not reach early childhood education that Europeans had in 1960. Moreover, the life expectation and total factor productivity were important for understanding the increasing the distance in per capita income between sub-Saharan and European countries. Finally, the main result in terms of educational policy is that policies to encourage early childhood education are more effective to increase the per capita income than policies encouraging formal education.